A Study on the Relationship Between Adolescent Health Behavior, BMI, and Blood Physical and Chemical Properties - Peng, Jie; Yin, Lian; Wang, Kun; Zhang, Tingran; Liu, Hengxu; Yang, Jinxin; Luo, Jiong (Frontiers in Public Health, 2022)
In this study, the blood test index, demographic data and health promotion behavior of adolescents were analyzed to provide reference for early prevention and treatment of physical decline and abnormal biochemical indexes of adolescents. Using cross-sectional study design, 1436 valid samples were obtained by stratified random sampling, and the data were processed by spss21.0 statistical analysis software. The results showed that the overall health promoting lifestyle of adolescents was good, and the interpersonal support behavior was the best, and the health responsibility and sports participation behavior was the worst; the interpersonal support and sports participation behavior of adolescents with normal weight was significantly better than those with overweight or light weight, while the overall health promoting behavior of adolescents with high fasting blood glucose (FBG) before meals was poor, those with high glutamate pyruvate transaminase (GPT) had poor nutritional behavior and health responsibility behavior, while those with high uric acid(UA) had poor interpersonal support and stress coping behavior; The overweight rate and abnormal detection rate of uric acid (UA) and triglyceride (TG) in boys were significantly higher than those in girls, and the higher BMI of teenagers, the higher abnormal detection rate of GPT, UA and TG, the better nutritional behavior, health responsibility behavior and sports participation behavior, the lower abnormal detection rate of GPT, UA and TG; the higher education level of parents, the better teenagers' sports participation and health responsibility behavior, the lower the incidence of overweight, the more time they spend playing online games and drinking sugary drinks on weekdays (or holidays), the higher the incidence of overweight.